2022
DOI: 10.1002/ajcp.12589
|View full text |Cite
|
Sign up to set email alerts
|

Informal supports, housing insecurity, and adolescent outcomes: Implications for promoting resilience

Abstract: Adolescents in low‐income, marginalized families are vulnerable to behavior problems that impede healthy functioning and threaten long‐term well‐being. Informal supports may fill an important gap for these households as they navigate financial and social stressors. Instrumental support from social networks and neighborhood cohesion may promote family stability and youth well‐being; further, these informal supports may promote resilience to housing insecurity, which is linked with a range of adverse adolescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Constructs such as neighborhood cohesion, collective efficacy, and neighborhood connectedness were identified as key factors. Neighborhood cohesion is defined as the degree to which neighbors are interconnected and supportive [64]. In neighborhoods with high collective efficacy, residents are more likely to take collective action on behalf of each other and the neighbor-hood as a whole [86,87].…”
Section: Neighborhood Advantagesmentioning
confidence: 99%
“…Constructs such as neighborhood cohesion, collective efficacy, and neighborhood connectedness were identified as key factors. Neighborhood cohesion is defined as the degree to which neighbors are interconnected and supportive [64]. In neighborhoods with high collective efficacy, residents are more likely to take collective action on behalf of each other and the neighbor-hood as a whole [86,87].…”
Section: Neighborhood Advantagesmentioning
confidence: 99%
“…Moreover, there were many studies that explored the relationship between PCEs and resilience. Marçal and Maguire-Jack ( 2022 ) discovered that neighborhood support could serve as a powerful resilience resource for teens. A review of adolescents of transgender and gender nonconforming (TGNC) found that good relationships with family members (especially with parents), social support except for parents, and better school safety or inclusive school climate promoted their resilience (Tankersley et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%